Eradication Efforts of Drug Abuse in Indonesia - Zulkarnain (Britain International for Academic Research (BIAR) Publisher, 2019)
The danger of drug abuse has now become a serious double threat that is the destruction of the future and life plus prolonged suffering without hope of recovery due to the destruction of the immune system. This study deals with the eradication efforts of drug abuse in Indonesia. The subject of this study is drug abuse in the perspective of Islamic Law based on revelation and in the perspective of Indonesian positive law. The approach used in this study is comparative through juridical normative-telogic. The result shows that the concept of prevention and tackling of drugs in Islamic law in the form of preventive, refresive and educative. Whereas in Indonesian positive law through law No. 35 of 2009 in the form of preventive, refresive, curative and educative efforts and has made compulsory provisions for the rehabilitation of addicts and victims of drug abuse.